Konstruksi makna pada simbol matematika dalam perspektif semiotika - Palayukan, Hersiyati; Palengka, Inelsi (IKIP Siliwangi, 2024)
The Semiotic process (construction of sign meaning) is very closely related to mathematics which consists of signs or symbols. This research aims to explore students' semiotic processes in constructing the meaning of symbols in whole numbers. This research is a qualitative descriptive research using a semiotic approach. The subjects in this research were selected using purposive sampling (purposeful sampling). The subjects in this research were 32 elementary school students. Based on this research, 5 types of semiotic construction patterns were obtained with each subject grouped based on its semiotic construction, namely 1) strong semiotic construction, 2) weak semiosis construction, 3) True-False semiotic construction, 4) False-True semiotic construction, and 5) False-False semiotic construction. The semiosis construction process is a determining factor in students understanding the signs of operations in integers.